2018
DOI: 10.1155/2018/4536707
|View full text |Cite
|
Sign up to set email alerts
|

Availability of Dental Prosthesis Procedures in Brazilian Primary Health Care

Abstract: Objectives To describe dental prosthesis provision in the Brazilian public health service and report the performance of dental prosthesis procedures according to the Brazilian macroregions. Methods A structured interview was conducted with senior-level health professionals from each of the 18,114 oral health teams (OHT). The dependent variables were performance of removable prostheses and prosthesis procedures, including provision of fixed prostheses by OHT. Descriptive statistics were produced together with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 22 publications
1
12
0
6
Order By: Relevance
“…However, concerning the procedures related to dental prostheses, although they identified people in the need, few are the OHT that reported the confection of it (6,7). In addition, evaluating data from the second cycle of PMAQ-AB, Cunha et al showed that the distribution of teams that performed dental prostheses across the country was unequal and, the provision was almost restricted to partial and total removable prostheses (8).…”
Section: Introductionmentioning
confidence: 99%
“…However, concerning the procedures related to dental prostheses, although they identified people in the need, few are the OHT that reported the confection of it (6,7). In addition, evaluating data from the second cycle of PMAQ-AB, Cunha et al showed that the distribution of teams that performed dental prostheses across the country was unequal and, the provision was almost restricted to partial and total removable prostheses (8).…”
Section: Introductionmentioning
confidence: 99%
“…In relation to the data which represents the majority of PHC nationally, it has been suggested that inadequate provision of dentures may be related to the unequal distribution of SUS regional prosthodontic laboratories throughout the country; even with the care almost restricted to partial/total dentures [26]. It is of concern that dental rehabilitation may not be adequately provided by the public sector, as the need for total/partial dentures and crown/bridges is still great among adults and the elderly [27], and our analysis suggests that these items are not available across SUS dental teams and supports the findings of Cunha et al [26]. It suggests that the population may be forced to use the private sector, or remain on waiting lists for long time, in order to receive necessary dental prosthetic treatment, which increases inequalities.…”
Section: Discussionmentioning
confidence: 99%
“…It suggests that the population may be forced to use the private sector, or remain on waiting lists for long time, in order to receive necessary dental prosthetic treatment, which increases inequalities. This is an area for urgent identification of the barriers to dental care for adults, together with the educational and training needs of the dental workforce so that service barriers can be overcome to ensure that the population has access to prosthodontics [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pesquisas demonstram desigualdades na distribuição geográfica dos serviços de prótese dentária pelo SUS [11][12][13] e seu acesso ainda é restrito levando em consideração a demanda populacional por reabilitação protética 11,14 . Dados do Programa de Melhoria do Acesso e da Qualidade da Atenção Básica apresentam que apenas 43% das Equipes de Saúde Bucal (ESB) no país realizam procedimentos de prótese dentária, e a maior proporção delas está localizada nas regiões Nordeste (33,9%) e no Sudeste (33,6%) 12 . Entretanto, ainda não existem publicações específicas deste serviço para o estado da Bahia.…”
Section: Palavras-chaveunclassified